2009
DOI: 10.1097/hco.0b013e32832cf8f6
|View full text |Cite
|
Sign up to set email alerts
|

3D echocardiography: evaluation of the right ventricle

Abstract: Despite the development of new real-time 3D echocardiographic systems, there still exist limitations in clinical settings due to technical factors. Thus, the combination of conventional 2D and Doppler methods and 3D echocardiography is recommended in the evaluation of the RV at the present time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
23
0
3

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(26 citation statements)
references
References 25 publications
0
23
0
3
Order By: Relevance
“…The introduction of 3DE enables the accurate quantitation of RV volumes, function, and mass, and this accuracy can be compared with the results of MRI, which still remains a gold standard for the RV evaluation (31,32). Additionally, 2DE speckle tracking imaging, unlike conventional tissue Doppler imaging, identifies RV and RA myocardial deformation during the whole cardiac cycle, providing information not only about global strain but regional as well, and it also represents a highly reproducible imaging tool which could easily be used in everyday clinical practice (33).…”
Section: Discussionmentioning
confidence: 99%
“…The introduction of 3DE enables the accurate quantitation of RV volumes, function, and mass, and this accuracy can be compared with the results of MRI, which still remains a gold standard for the RV evaluation (31,32). Additionally, 2DE speckle tracking imaging, unlike conventional tissue Doppler imaging, identifies RV and RA myocardial deformation during the whole cardiac cycle, providing information not only about global strain but regional as well, and it also represents a highly reproducible imaging tool which could easily be used in everyday clinical practice (33).…”
Section: Discussionmentioning
confidence: 99%
“…Three-dimensional echocardiography allows the quantification of volumes and function in normal subjects and patients, 72 thereby allowing identification of patients with different degrees of severity of RV dilatation and dysfunction. 73 Several clinical studies have shown a good correlation between cardiac magnetic resonance and 3DE volumes and ejection fraction of the right ventricle in selected populations, with the majority of studies showing a slight underestimation of volumes compared with the reference technique.…”
Section: E Clinical Validation and Applicationmentioning
confidence: 99%
“…Three-dimensional transthoracic echocardiography (3DTTE) has the advantage of full-volume acquisition of the entire right ventricle, which may overcome the technical and clinical limitations of 2-dimensional transthoracic echocardiography. [10][11][12] Recent studies have validated the accuracy of 3DTTE-determined RV volumes and RVEF against CMR 13,14 and determined the reference values of RV volumes and RVEF in healthy subjects. 15,16 However, the prognostic value of RVEF is largely unknown.…”
mentioning
confidence: 99%